Hubungan Indeks Massa Tubuh Dan Glukosa Darah Dengan Laju Filtrasi Glomerulus Pada Pasien Diabetes Mellitus Di RSI- Sultan Agung Semarang - Dewi Maulina Maulina; Dwi Retno Sulistyaningsih; Retno Setyawati (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah., 2025)
ABSTRACT Background: Diabetes mellitus is a condition where the body's glucose metabolism is disrupted. Hormonal issues lead to a variety of metabolic illnesses, which in turn produce abnormal insulin levels and other chronic complications. One of the triggers for diabetes mellitus is body mass index, blood glucose. DM sufferers can affect kidney function which results in the accumulation of blood creatinine and urea levels which can cause kidney failure. Glomerular filtration rate as the best index to assess kidney function parameters. Method: quantitative approach combined with a cross-sectional investigation. Purposive sampling was used to choose a sample of 82 individuals. The Spearman rank test was used to statistically process the data. Results: the average glomerular filtration rate value was 42.24 ml/min/1.73 m2 (SDÂ±23,478). Conclusion: A weak correlation (r) of -0.386 and a p value <0.05, or 0.000, indicate a link between body mass index and glomerular filtration rate. Because of the negative association, the glomerular filtration rate value decreases as the body mass index value increases. The association between random blood glucose and glomerular filtration rate in individuals with diabetes mellitus, on the other hand, is 0.000 with a moderate correlation value (r) of -0.490 and a p value <0.05. Because of the negative association, the filtration rate value decreases as blood glucose levels rise. Keywords: body mass index, blood glucose, glomerular filtration rate